Features of sensitization to food allergens in children who were on BLW supplementation - K.I. Tarshina; O.V. Sharikadze; S.O. Zubchenko (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. The prevalence of food allergy (FA) is rapidly increasing, particularly among young children. The introduction of complementary feeding is a critical period for the development of immune tolerance to food allergens. Baby-led weaning (BLW), a feeding method that allows infants to self-feed, may potentially alter the sensitization profile to allergens. However, the impact of BLW on FA development remains insufficiently studied.